2017
DOI: 10.1111/jog.13546
|View full text |Cite
|
Sign up to set email alerts
|

Randomized control trial comparing effectiveness of weekly versus daily antenatal oral iron supplementation in preventing anemia during pregnancy

Abstract: In non-anemic pregnant women, a weekly regimen is an effective alternative to a daily regimen for antenatal oral iron and folate supplementation for preventing anemia and iron deficiency during the third trimester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
1
6
0
3
Order By: Relevance
“…The difference of ferritin serum before and after iron supplementation between daily and weekly group was not statistically different (p = 0.917). This result was similar with the study by Goonewardene and Senadheera [12], [19]. Several studies showed changes of ferritin serum level after iron supplementation in daily and weekly group [14], [20], [21], [22].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The difference of ferritin serum before and after iron supplementation between daily and weekly group was not statistically different (p = 0.917). This result was similar with the study by Goonewardene and Senadheera [12], [19]. Several studies showed changes of ferritin serum level after iron supplementation in daily and weekly group [14], [20], [21], [22].…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed decreasing level in hemoglobin before and after iron supplementation in the daily group as well as the weekly group, but it was not statistically significant. The change of hemoglobin concentration was not statistically different between daily and weekly groups (p = 0.421) A recent study found that in non-anemic pregnant women, the weekly iron supplementation was an effective alternative to the daily supplementation for preventing anemia and iron deficiency [19]. The weekly iron supplementation benefits pregnant women in serum iron and total iron binding capacity (TIBC) [20]; therefore, iron deficiency anemia in pregnant women can be prevented.…”
Section: Discussionmentioning
confidence: 97%
“…Demir metabolizmasının ve hepsidinin buradaki görevinin son yıllarda daha da anlaşılması yeni ara- lıklı tedavi ve profilaksi yaklaşımlarını doğurmuştur. Yalnızca çocuk ve erişkinlerdeki anemi tedavisi için değil, anemik olmayan çocuklarda ve gebelerde de haftalık ya da aralıklı demir profilaksisi günlük uygulamaya alternatif etkili bir yöntem olarak sunulmuştur (25)(26)(27) . Bu konuda ülkemizde ve dünyada yapılmış bazı çalışmalarda, bu hipotez desteklenmekte, ortaya çıkan net etkinin günlük tedaviden farklı olmadığı, uyumun daha iyi olduğu ve yan etkilerin de daha az gözlendiği bildirilmektedir (12,19,21,22,28) .…”
Section: Discussionunclassified
“…Различные исследования показа-ли, что последняя превосходит пероральную с точки зрения скорости и абсолютной степени увеличения гемоглобина [7,17,23,24]. В I триместре беременности внутривенное введение железа противопоказано.…”
Section: беременность и родыunclassified
“…Любой установленный железодефицит во время бере-менности должен предполагать его коррекцию [4,17,18,23,24]. Необходимо понимать, что железосодержащая диета назначается, но купировать недостаток железа только с ее помощью невозможно.…”
unclassified